2019
DOI: 10.1021/acs.jmedchem.9b01411
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Salicylic Acid-Derived Sulfonamide Inhibitors of the WD Repeat-Containing Protein 5–MYC Protein–Protein Interaction

Abstract: The treatment of tumors driven by overexpression or amplification of MYC oncogenes remains a significant challenge in drug discovery. Here, we present a new strategy towards the inhibition of MYC via the disruption of the protein-protein-interaction between MYC and its chromatin cofactor WDR5. Blocking the association of these proteins is hypothesized to disrupt the localization of MYC to chromatin, thus disrupting the ability of MYC to sustain tumorigenesis. Utilizing a high-throughput screening campaign and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 54 publications
1
81
0
Order By: Relevance
“…From Figure 3 , we can realize that the arginine residue stretches into the deep pocket of WIN site, which formed extensive hydrogen bonding interactions with nearby residues and water molecules. Comparing to WDR5 bound with a peptide segment from MLL2 (PDB ID: 3UVK) [ 25 ], it was found that the arginine residue from MLL2 is located at the exact same position as in our solved structure, further indicating it is important for the binding interactions ( Supplementary Information see Figure S4 ). Besides, the positive-charge nature of guanidyl group sandwiched between two aromatic residues Phe133 and Phe263, forming the typical cation-Pi interactions.…”
Section: Resultsmentioning
confidence: 78%
“…From Figure 3 , we can realize that the arginine residue stretches into the deep pocket of WIN site, which formed extensive hydrogen bonding interactions with nearby residues and water molecules. Comparing to WDR5 bound with a peptide segment from MLL2 (PDB ID: 3UVK) [ 25 ], it was found that the arginine residue from MLL2 is located at the exact same position as in our solved structure, further indicating it is important for the binding interactions ( Supplementary Information see Figure S4 ). Besides, the positive-charge nature of guanidyl group sandwiched between two aromatic residues Phe133 and Phe263, forming the typical cation-Pi interactions.…”
Section: Resultsmentioning
confidence: 78%
“…So manual test is feasible, but for a limited number of samples. We took ten articles [28][29][30][31][32][33][34][35][36][37] to test our method on the real data. Structures that represent reaction mechanisms were excluded, so we regarded only molecules and Markush templates.…”
Section: Validation On Real Datamentioning
confidence: 99%
“…28 Recently, first MYC/WDR5 protein-protein interface inhibitors have been developed. 15,29 The WDR5 WIN site, located opposite the MYC binding site, is required for WDR5 chromatin recruitment and interaction with KMT2 enzymes, and MLL1 is a particularly dependent on this interaction. The small molecule antagonist OICR-9429 for instance binds to the WIN site of WDR5, and efficiently disrupts its interaction with MLL1.…”
Section: Introductionmentioning
confidence: 99%